Identification of preferred carbohydrate binding modes in xenoreactive antibodies by combining conformational filters and binding site maps - Agostino, Mark; Sandrin, M.; Thompson, P.; Yuriev, E.; Ramsland, Paul (Oxford University Press, 2010)
Carbohydrates are notoriously flexible molecules. However, they have an important role in many biochemical processes as specific ligands. Understanding how carbohydrates are recognized by other biological macromolecules (usually proteins) is therefore of considerable scientific value. Interfering with carbohydrate-protein interactions is a potentially useful strategy in combating a range of disease states, as well as being of critical importance in facilitating allo- and xenotransplantation. We have devised an in silico protocol for analyzing carbohydrate-protein interactions. In this study, we have applied the protocol to determine the structures of aGal-terminating carbohydrate antigens in complex with a panel of xenoreactive antibodies. The most important feature of the binding modes is the fixed conformation of the Galß(1,4)Glc/GlcNAc linkage across all of the binding modes. The preferred conformation of the terminal Gala(1,3)Gal linkage varies depending on the antibody binding site topography, although it is possible that some of the antibodies studied recognize more than one Gala(1,3)Gal conformation. The binding modes obtained indicate that each antibody uses distinct mechanisms in recognizing the target antigens. © The Author 2010. Published by Oxford University Press. All rights reserved. For permissions, please e-mail: journals.permissions@oxfordjournals.org.